THE EFFECT OF CANVA AND WORDWALL LEARNING MEDIA IN HISTORY SUBJECTS ON STUDENTS' LEARNING ACHIEVEMENTS OF CLASS X AKL 1 SMK 02 ISLAM 45 AMBULU IN THE YEAR OF 2024/2025: Pengaruh Media Pembelajaran Canva Dan Wordwall Pada Mata Pelajaran Sejarah Terhadap Prestasi Belajar Siswa Kelas X Akl 1 Smk 02 Islam 45 Ambulu Tahun 2024/2025 - Intan Wahyuningtyas; Ilfiana Firzaq Arifin; Mohamad II Badri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to examine the effect of using Canva and Wordwall learning media on the learning achievement of class X AKL 1 students at SMK 02 Islam 45 Ambulu. The main focus of the study is to determine the extent to which the media affects student learning achievement. The method used is quantitative with the True Experimental Design approach, which allows researchers to control all external variables during the experimental process. The research design used is Pretest-Posttest Control Group Design involving two groups, namely the experimental class and the control class, to test the hypothesis that the use of Canva and Wordwall has a significant impact on learning achievement. Data collection was carried out through tests designed to measure student learning achievement. All data were then analyzed using scoring techniques and then conducting normality tests, homogeneity tests, and hypothesis tests, which were processed with the help of the SPSS version 25 application. The results showed that the control class obtained the highest score of 85 while the experimental class after being treated achieved a higher score of 90. From the hypothesis test, a significance value of 0.009 was obtained which was smaller than the limit of 0.05, so H0 was rejected and Ha was accepted. This indicates a significant difference between the two classes. Thus, it can be concluded that the use of Canva and Wordwall learning media has a positive influence on